PENILAIAN EKONOMI PENANGKARAN RUSA DI TAMAN HUTAN RAYA WAN ABDUL RACHMAN (TAHURA WAR) MENGGUNAKAN METODE KESEDIAAN MEMBAYAR - Kahimpong, Kevin Ewaldo (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Lampung is one of the provinces that has various tourist objects, one of which is the Deer Breeding in Wan Abdul Rachman (WAR) Grand Forest Park (Tahura). Its use as a tourist attracts visitors to come and have recreation. As one of the efforts for sustainable use, it is necessary to carry out an economic valuation. The purpose of this study was to calculate the willingness to pay visitors to the Deer Breeding in Tahura WAR using the willingness to pay method and to estimate the revenue received from the tourist attraction of Tahura WAR Deer Captivity. The method used in this research is the willingness to pay method with the contingent valuation method (CVM) and the total revenue method. The research was conducted from February to March 2020. The respondents selected regarding the purposive sampling method that was 100 people. The results showed that the average value of the willingness to pay visitors in Tahura WAR Deer Breeding was Rp. 12.900,-/person/visit, and acceptance of the Tahura WAR Deer Breeding was Rp. 27.552.00.000,-/year the value obtained from the willingness to pay visitors to a hypothetical market in the form of making deer conservation education packages.